Determinants of audit report lag among Malaysian public listed companies during the convergence period of IFRS - Kogilavani, Apadore (2022)
The nature of the Corporate Governance mechanism in a company may influence the timeliness of the audited financial statement. This study examines the trend of Audit Report Lag (ARL) as well as its relationship with Audit Committee Characteristic, Board Characteristics, internal audit investment and internal audit sourcing arrangement (outsourcing) within Malaysia Public Listed Companies. The investigation is on the data gathered from 2011 until 2015 during the IFRS Convergence period compared to previous literature, which was up to 2012 data only. This study utilises balanced panel data for a sample of 342 listed companies, with 1710 observations. Data were collected through annual reports obtained from the Bursa Malaysia website. The results showed a significant association between ARL and audit committee chair’s position and the audit committee’s training, experience, gender, and size. This study also discovered that an audit committee with adequate training in the financial area, increasing women membership in the audit committee, larger size of the audit committee and the chair with multiple positions strengthen the responsibilities and work experiences of Audit Committee Chairs. Therefore, this study adds on new contrast in addition to commonly studied Corporate Governance Characteristics. Thus, it translates to a governed work culture that resulted in the reduction of ARL. Nevertheless, this study found an insignificant relationship between ARL and Board Characteristics. Also, the results showed that high internal audit investment could enhance better monitoring, improve accuracy and confidence level towards Financial Statements, and reduce the ARL. On the contrary, this study demonstrated that audit committee members with more than three years of accounting and finance experience and outsourcing of internal audit function is essential, and it is not adequate to push for a reduction in ARL. This study offers valuable insights for all stakeholders, including policymakers, regulators, academics, the board of directors, and the audit committee, in ensuring the code of corporate governance is properly governed according to Bursa Malaysia requirements. This study recommends a higher composition of female audit committee members, providing suitable training within the financial area, and engaging the audit committee chair with multiple positions to enhance a company's corporate governance, primarily concerning the audit report lag.